The path of worshippers to the paradise of the lord of the worlds = Minhāj al-ʻābidīn ilā jannat rabb al-ʻālamīn - Ghazzālīd (University Press of America Oxford Publicity Partnership [distributor], 2012)
The Path of Worshippers to the Paradise of the Lord of the Universe is an authoritative book and a guideline on practical Sufism ('irfan-i 'amali). It is also a mirror to the soul of its author. In this book Ghazzālī speaks not only as a scholar but also as a master and sincerely shares his spiritual experiences with his readers in a simple language and an intimate tone. These qualities of the book penetrate into the depth of the heart of the reader. The importance of the book lies in the fact that its author was the most prominent theologian and jurist of his time and its teachings are as valid today as they were when the author wrote the book just before his death in 505/1111